Современные архангельские говоры: сопоставление двух частных диалектных систем(On two contemporary Archangel’sk dialects) - Savelova, L. A. (Poljarnyj vestnik, 1998)
This article presents two dialects found in the Archangel’sk oblast’, namely the dialect of the Verkhnetoemsky region and that of the Primorsky region. The "maternal base", i.e. the geographical origin, of these dialects is dis- cussed. The most important phonetic and morphological features of the dialects are compared with the corresponding features in other contempor- ary Russian dialects and in the language of Old Novgorod. The main features distinguishing the two dialects are: 1) the realization of /a/ end /e/ (from ®) under stress between soft consonants; 2) the development of soft "cokanje"; 3) differences in morphology concerning: a) the singular dative and prepositional of I decl. nouns; b) the plural instrumental of nouns and adjectives; c) the singular masc.-neutr. genitive of adjectives; d) the 3rd person sing. of I conjug. verbs and the 3rd person plur. of II conjug. verbs.